Post - traumatic stress disorder for women displaced in camps South Darfur State - Sudan - Bishara, Iman AbdulRasool Mohammed; Khalifa, Yasser Hassan Ahmed (Arab Journal for Sciences and Research Publishing, 2017)
This research aimed at knowing the post-traumatic stress disorders in a sample of women displaced camps in South Darfur state. The researcher used the descriptive method. The sample of the study was composed of the displaced women in the camps of South Darfur state. The researcher applied the measurements. The size of the sample was (500) displaced women. They were chosen according to the purposive sampling method. Research tools are represented by the measurement of the post-traumatic stress disorder. The data were analyzed by using the statistical packages for social sciences (SPSS).       The research findings are as the following:There is a positive correlation in post-traumatic stress disorder for displaced women in South Darfur state camps according to the research demographic variables (social status, qualification, age, time passed in the displacement camps) in all dimensions and total score, except after high excitement and avoiding thinking.*Extracted research paper from a PhD thesis in the Department of Psychology - Faculty of Arts - Omdurman Islamic University. Entitled "Post-Traumatic Stress Disorder and its Relationship to some Personality Traits of Displaced Women in the Camps of South Darfur State" by: Dr. Iman Abdul Rasul Muhammad Bishara.
Keywords: disorder; stress; trauma; women; displaced people